DNA microarray reveals changes in gene expression of shear stressed human umbilical vein endothelial cells - McCormick, Susan M. (The National Academy of Sciences, 2001)
Using DNA microarray screening (GeneFilter 211, Research Genetics, Huntsville, AL) of mRNA from primary human umbilical vein endothelial cells (HUVEC), we identified 52 genes with significantly altered expression under shear stress [25 dynes/cm(2) for 6 or 24 h (1 dyne = 10 μN), compared with matched stationary controls]; including several genes not heretofore recognized to be shear stress responsive. We examined mRNA expression of nine genes by Northern blot analysis, which confirmed the results obtained on DNA microarrays. Thirty-two genes were up-regulated (by more than 2-fold), the most enhanced being cytochromes P450 1A1 and 1B1, zinc finger protein EZF/GKLF, glucocorticoid-induced leucine zipper protein, argininosuccinate synthase, and human prostaglandin transporter. Most dramatically decreased (by more than 2-fold) were connective tissue growth factor, endothelin-1, monocyte chemotactic protein-1, and spermidine/spermine N1-acetyltransferase. The changes observed suggest several potential mechanisms for increased NO production under shear stress in endothelial cells.